Wavelength-tunable picosecond soliton fiber laser with topological insulator : Bi2Se3 as a mode locker - Zhao, Chujun (2013)
Based on the open-aperture Z-scan measurement, we firstly uncovered the saturable absorption property of the topological insulator (TI): Bi2Se3. A high absolute modulation depth up to 98% and a saturation intensity of 0.49 GWcm−2 were identified. By incorporating this novel saturable absorber material into an erbium-doped fiber laser, wavelength tunable soliton operation was experimentally demonstrated. Our result indicates that like the atomic layer graphene, the topological insulator Bi2Se3 could also operate as an effective saturable absorber for the passive mode locking of lasers at the telecommunication band.